Games of deception : the true story of the first U.S. Olympic basketball team at the 1936 Olympics in Hitler's Germany - Maraniss, Andrew (Philomel Books, 2019)
"The true story of the birth of Olympic basketball at the 1936 Summer Games in Hitler's Germany"--